Comparison of neurotoxic effects of ethanol and endosulfan on biochemical changes of brain tissues in Javanese medaka (Oryzias javanicus) and zebrafish (Danio rerio) - Ramlan, Nurul Farhana (Universiti Putra Malaysia Press, 2020)
An ideal model organism for neurotoxicology research should meet several characteristics, such as low cost and amenable for high throughput testing. Javanese medaka (JM) has been widely used in the ecotoxicological studies related to the marine and freshwater environment, but rarely utilized for biomedical research. Therefore, in this study, the applicability of using JM in the neurotoxicology research was assessed using biochemical comparison with an established model organism, the zebrafish. Identification of biochemical changes due to the neurotoxic effects of ethanol and endosulfan was assessed using Fourier Transform Infrared (FTIR) analysis. Treatment with ethanol affected the level of lipids, proteins, glycogens and nucleic acids in the brain of JM. Meanwhile, treatment with endosulfan showed alteration in the level of lipids and nucleic acids. For the zebrafish, exposure to ethanol affected the level of protein, fatty acid and amino acid, and exposure to endosulfan induced alteration in the fatty acids, amino acids, nucleic acids and protein in the brain of zebrafish. The sensitive response of the JM toward chemicals exposure proved that it was a valuable model for neurotoxicology research. More studies need to be conducted to further develop JM as an ideal model organism for neurotoxicology research.